Islamic Bond Issuance : What Sovereign Debt Managers Need to Know - Sy, Amadou; Jobst, Andreas; Kunzel, Peter; Mills, Paul. (Washington, D.C. : International Monetary Fund, 2008)
Recent years have witnessed a surge in the issuance of Islamic capital market securities (sukuk) by corporates and public sector entities amid growing demand for alternative investments. As the sukuk market continues to develop, new challenges and opportunities for sovereign debt managers and capital market development arise. This paper reviews the key developments in the sukuk market and informs the debate about challenges and opportunities going forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet